ERK2-ZEB1-miR-101-1 axis contributes to epithelial–mesenchymal transition and cell migration in cancer. (10th April 2017) - Chandra Mangalhara, Kailash; Manvati, Siddharth; Saini, Sunil Kumar; Ponnusamy, Kalaiarasan; Agarwal, Gaurav; Abraham, Suresh K.; Bamezai, Rameshwar N.K.
Abstract: Regulation of metastasis continues to remain enigmatic despite our improved understanding of cancer. Identification of microRNAs associated with metastasis in the recent past has provided a new hope. Here, we show how microRNA-101 (miR-101) regulates two independent processes of cellular metastasis by targeting pro-metastatic upstream regulatory transcription factors, ZEB1 and ZEB2, and downstream effector-actin modulators, RHOA and RAC1, providing a single target for therapeutic intervention. Further, we depict how down-regulation of miR-101 by extracellular signal-regulated kinase-2 (ERK2) is vital for MAP kinase pathway induced cellular migration and mesenchymal transition. Importantly, EKR2 induced expression of ZEB1 seems essential for down-regulation of miR-101-1 and induction of EMT. Given the role of EMT in metastasis, we also observe a significant correlation between miR-101 expression and lymph node metastasis; and identify the ERK2-ZEB1 - miR-101-1 pathway active in breast cancer tissues, with an apparent clinicopathological implication. Graphical abstract: Highlights: miR-101, down-regulated by EGF, targets RHOA, RAC1, ZEB1, and ZEB2. Activation of ERK2-Zeb1-miR-101-1 axis is crucial for EMT and cell migration. miR-101 is a common regulator of both EMT-TFs and actin cytoskeleton modulators. ERK2-Zeb1-miR-101-1 axis is active in cell lines and studied tumor tissues.